Zamykanie i rekultywacja dzikich składowisk odpadów niespełniających wymagań prawnych po wejściu Polski do UE na przykładzie wybranego składowiska z terenu powiatu nowosądeckiego = The closing and remediation of the non-regulated landfills non-conforming with legal requirements after the joining of Poland to EU, on the example of a selected landfill at the territory of Nowy Sącz district - Mamak, Magdalena; Kicińska, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work, the most important issues related to legal aspects of closing and remediation of landfills used for storage of waste other than hazardous and inert waste, which means mainly for municipal waste storage, are considered. The work also refers to the required monitoring which should be performed in post-operation period. The analysis and evaluation of such process has been performed upon the example of the selected inoperable landfill located at the territory of Nowy Sącz district.
Keywords: składowisko odpadów; proces rekultywacji; prawo; monitoring; landfill; remediation process; legal requirements